Are highly unionised industries socially responsible to their employees? - Mara Ridhuan Che Abdul Rahman,; Insyira Afika Ibrahim,; Dina Mardinah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Corporate social responsibility towards employees (CSR-E) is a vital aspect of modern business that can promote employee rights, justice and standards of employment, which in turn can generate benefits for companies. From the perspective of stakeholder theory, companies are expected to act and react to the demands of their most powerful stakeholders. Therefore, previous studies on CSR-E are skewed towards employees, whom they view as relevant and powerful stakeholders, and view CSR-E as a tool for promoting employee engagement. However, these studies have neglected the labour union power of stakeholders over the CSR-E activities of companies, particularly in Malaysia. The presence of labour unions can increase the tendency for a company to observe a state of democracy, and the negotiation and collective bargaining power of these labour unions can narrow the gap between the expectations of employees and their companies. Nonetheless, the relationship between labour unions and CSR-E is only based on gut feeling and has never been examined in the Malaysian context. Given the differences in unionisation rates across industries, this study predicts that highly unionised industries practise CSR-E to a greater extent compared with non-unionised ones. Therefore, this study examines the relationship between highly unionised industries and CSR-E practice. Banking and financial institutions and real estate and properties were selected as highly and poorly unionised industries in this paper, respectively, and their ratings were calculated based on available data from the Malaysian Trade Union Congress. A total of 100 annual reports for financial years ending in 2017 and 2018 were gathered from 50 companies and were analysed for their content to measure CSRE. Control variables, including size, profit and leverage, were also used to examine the relationship between CSR-E and unionisation. Highly unionised industries demonstrated a positive relationship with CSR-E practice.